A new look at the Y tetraquarks and $$Ω _c$$ Ωc baryons in the diquark model - Ahmed Ali (European Physical Journal C: Particles and Fields, 2018)
Abstract We analyze the hidden charm P-wave tetraquarks in the diquark model, using an effective Hamiltonian incorporating the dominant spin–spin, spin–orbit and tensor interactions. We compare with other P-wave systems such as P-wave charmonia and the newly discovered $$Ω _c$$ Ωc baryons, analysed recently in this framework. Given the uncertain experimental situation on the Y states, we allow for different spectra and discuss the related parameters in the diquark model. In addition to the presently observed ones, we expect many more states in the supermultiplet of $$L=1$$ L=1 diquarkonia, whose $$J^{PC}$$ JPC quantum numbers and masses are worked out, using the parameters from the currently preferred Y-states pattern. The existence of these new resonances would be a decisive footprint of the underlying diquark dynamics.